Strategi Pemasaran Syariah UMKM untuk Produk Unggulan Daerah: Sale Pisang Khas Bungo di Tengah Disrupsi Pasar Multi Saluran (Online, Offline) - Habib Hidayatullah; Siti Wulandari; Okta Dina; Muhammad Zaki; Mabruri Mabruri (Trending: Jurnal Manajemen dan Ekonomi, 2026)
In the Indonesian economy, Micro, Small and Medium Enterprises or MSMEs are the business group that has the largest number and is proven to be resistant to various kinds of shocks to the economic crisis. Micro, Small, and Medium Enterprises (MSMEs) are encouraged to be able to develop into the global market not only on a national scale. The strategy is very important to determine the success of a company to achieve its long-term goals. By choosing the right strategy for a particular company position, it will make a company have a competitive advantage. The purpose of this research is to find out what is the most appropriate strategy that should be taken as a UMKM in facing Global Business competition From the research results, it can be seen from the perspective of Islamic marketing strategy, apart from applying conventional marketing strategies, he also implements sharia marketing strategies which consist of three main points, namely firstly applying Shariah marketing characteristics based on the Qur’an and As-Sunnah; second, the application of business ethics in Islam; third, following marketing according to what has been taught by the Prophet Muhammad, namely siddiq, amanah, fathanah and tabligh.